Effect of core corrugation angle on static compression of self-reinforced PP sandwich panels and bending energy absorption of sandwich beams. (March 2021) - Imran, Ali; Qi, Shijie; Shi, Pengcheng; Imran, Muhammad; Liu, Dong; Zhu, Yingdan; Yang, Guilin
The structural weight of an electric vehicle and its material's recyclability are the important parameters to optimize the overall cost as well as the mileage of a vehicle. Self-reinforced polymer composites (SRCs) can be potentially used for these applications because of their 100% recyclability as compared with multicomponent traditional epoxy matrix based fibre reinforced composites. In case of SRCs the fibres and matrix are synthesized from same family of polymers. An optimization study is required based on integration of material and structural parameters to reduced overall weight of the vehicles while keeping the strength up to the safety mark. We fabricated self-reinforced polypropylene (SrPP) sandwich structures through an ex-situ consolidation based fabrication method. An FEA based study was conducted to optimize the effect of core corrugation angle of sandwiched structures on out of plane compressive strength and flexural strength of SrPP sandwiched beams. The finite element study was preferred in order to save the experimental cost. Beams with 60° core corrugation angle have optimal flexural properties. The sandwiched panels with 45° corrugated core exhibited optimal stiffness while maximum energy absorption capacity was shown with 60° corrugated core sandwiched structures.